The Potential of Sumatran Pine Rosin for Reinforcement-Steel Coating in Wet Environment - Rudi Hartono; Bagyo Yanuwiadi; Lukman Hakim (Graduate Program, 2018)
The corrosion of reinforcement-steel is commonly prevented by applying hydrophobic coating. In this work, the potential of residual product from Sumatran Pine sap distillation, known as Sumatran pine rosin or gondorukem, as a natural and environmentally-friendy resource to coat reinforcement-steel, and an initial assessment on its capability to prevent the corrosion in wet environment were investigated. The experiments were performed using two types of commercially available gondorukem, namely type T and U. The coated reinforcement-steel samples were immersed in collected rainwater and their physical changes were observed periodically for 60 days. The results showed that gondorukem improve the durability of the reinforcement-steel from corrosion in a severe rainwater contact.Keywords: corrosion, coating, gondorukem, hydrophobic, pine rosin, reinforcement bar